2018
DOI: 10.21608/egyfs.2018.65838
|View full text |Cite
|
Sign up to set email alerts
|

Value of measurement of maternal serum alpha fetoprotien in diagnosis of pathologically adherent placenta in cases of placenta pravia

Abstract: Objective: to investigate the significance of elevated MSAFP in diagnosing pathologically adherent placenta among women with placenta previa and its predictive value for pregnancy outcome.Study Design: A retrospective study involved eighty women with placenta praevia divided into 4 equal groups according the degree of invasion as suspected by TAS, Doppler and MRI studies and confirmed postoperatively by histo-pathological examination. G1; included those with placenta pravia alone G2; those with placenta accret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
(25 reference statements)
0
2
0
Order By: Relevance
“…When the placenta is implanted, alpha-fetoprotein in fetal blood will directly enter maternal blood circulation, so AFP in maternal serum increases, up to 2–5 times that of normal pregnant women. 48 Morlando et al 49 found that the serum AFP and β-hCG at 14–22 weeks were higher in cases of the PAS, while Fyala et al 50 found that elevated third-trimester maternal serum AFP levels could predict PAS in placenta previa patients.…”
Section: Diagnosis Of Placenta Accreta Spectrummentioning
confidence: 99%
See 1 more Smart Citation
“…When the placenta is implanted, alpha-fetoprotein in fetal blood will directly enter maternal blood circulation, so AFP in maternal serum increases, up to 2–5 times that of normal pregnant women. 48 Morlando et al 49 found that the serum AFP and β-hCG at 14–22 weeks were higher in cases of the PAS, while Fyala et al 50 found that elevated third-trimester maternal serum AFP levels could predict PAS in placenta previa patients.…”
Section: Diagnosis Of Placenta Accreta Spectrummentioning
confidence: 99%
“… Morlando et al 49 2020 Second (14–22 weeks) AFP, β-hCG N/A Review AFP and β-hCG were both high. Fyala et al 50 2018 Third AFP 80 Retrospective Elevated AFP levels in serum could predict PAS. None.…”
Section: Diagnosis Of Placenta Accreta Spectrummentioning
confidence: 99%